Bangladesh’s Paradoxical Youth: Unfolding University Students’ Contradictory Perspectives on Secularism - Hossain, Md. Akmal (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
Secularism, dharmanirapekkhta in Bangla, is enshrined in the constitution of Bangladesh as one of the state principles in 1972. It stresses that all religious groups are independent in observing their faiths without fear or restriction. However, in Bangladesh, the concept of secularism has become an issue of contention between secularists and religious groups, particularly among university students. This paper is aimed at investigating the contradictory perspectives of university students on secularism in Bangladesh, as well as understanding the issue from socio-political, cultural, and religious perspectives. This study employed a qualitative research design, including convenience surveys and secondary content analysis, to address the research gap and test a hypothesis regarding the youths’ perception of secularism. The study found a paradoxical view of secularism. The study findings indicate that more than half of the students prefer secularism as one of Bangladesh’s state principles. In contrast, they view secularism negatively from Bangladesh’s socio-economic and political perspectives.